MANAJEMEN STRATEGIS PADA ORGANISASI NON PROFIT (ONP) - Muallief Umar (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2021)
This article intends to conduct counter discourse by focusing on the discussion of the implementation of strategic management in ONP as a "requirement" to become a social entity that helps overcome various community problems. The method used in this article is a literature review by collecting relevant literature, then analyzing, comparing, and drawing common ground to get a complete understanding. Fifteen articles related to ONP were found; nine discuss financial management including accountability and transparency, three discuss strategic management and quality management, one examines public relations and publicity, one discusses engagement in society, and one presents a critique of strategic management in ONP. Furthermore, the results of the study of this article are threefold, namely: first, the concept of ONP as an organization that was founded with the intention not to seek and accumulate profits, but to help overcome community problems on the basis of volunteerism, partnership, and humanity. Second, strategic management is very relevant to be applied to ONP. Practically, there are two strategic management models, namely the comprehensive Fred R. David model with a three-stage cycle and the Wheelen and Hunger model with a four-stage cycle. Third, there are two crucial challenges that must be answered by ONP, namely: 1) commitment and consistency in carrying out accountability and transparency in performance, and 2) firmness and sustainability in participation in realizing social welfare.